PARATE EKSEKUSI HAK TANGGUNGAN SEBAGAI SARANA UNTUK MENGATASI KREDIT MACET (Tinjauan Yuridis Menurut Hukum Perdata) - Abd. Rahmad; Joni Zulhendra (TAQNIN: Jurnal Syariah dan Hukum, 2022)
This paper aims to describe the execution of mortgage rights as a means of overcoming bad debts in a review of civil law. The focus of this research is how creditors decide on the implementation of mortgage execution in overcoming bad credit? What is the model for implementing parate execution of debt guarantees by debtors? This type of research is library research with an emphasis on information sources derived from legal books, articles, journals and literature that are relevant and aligned with the object of this research. The results of the study show that the execution of mortgage rights is carried out through a public auction mechanism by maximizing the efforts made by creditors in collecting their receivables either persuasively or by giving subpoenas/warnings. The execution model of the Debtor's debt guarantee through the Public Auction mechanism is carried out through the stages, namely verification of the document for the auction request for execution of the Mortgage by the auctioneer, determining the schedule for carrying out the auction. auction parate execution, fourth stage of verification of prospective bidders, fifth stage of auction implementation and determination of winners and sixth stage of making legal products in the form of minutes of auction.